Audit Services on the ICO Market: Opportunities and Prospects - Redchenko K. І. (Statistics of Ukraine, 2018)
Initial Coin Offering (ICO) has been one of the most popular ways of raising funds for investment projects and start-ups in the latest years. This generates demand for audit services intended to provide independent assessment of blockchain projects and consult emitting companies on ICO marketing issues. However, auditors demonstrate professional caution, expecting for reactions of regulators and for the establishment of clear rules on circulation of crypto currencies. The objective of the study is to review the existing practice of audit services at the ICO market and substantiate the risk-oriented approach to assessment of ICO projects. It is found out that applications of the blockchain technology open up two main prospective areas for auditors. The first one involves applications of blockchain in recording systems, thus offering new opportunities for getting confidence or executing coordinated procedures concerning financial reports of clients. The second one involves creating new services addressed to companies either applying blockchain technologies or operating in markets of crypto currencies and related financial instruments. The ICO market has featured the rapidly growing numbers of failures of emitting companies to fulfill their obligations and frauds, which makes the need for independent audit services even more pronounced. The entrance of audit firms in a risky, but attractive segment of “token” economy is, therefore, just a matter of time. The most promising activities related with blockchain technologies and ICO are audit of smart contracts, consulting in issues of token emission and investment, operation with crypto currencies and other financial instruments inherent in the virtual economy.